Fragility analysis of prestressed thin-walled aqueducts subjected to underwater explosions - Peng, Tao; Wang, Gaohui; Lu, Wenbo; Chen, Ming; Yan, Peng; Yang, Guangdong (Structures (Oxford), 2025)
The safety assessment of prestressed aqueducts is a crucial subject that has been investigated in recent years. It is a challenge to conduct a safety evaluation for prestressed aqueducts against underwater explosions due to the thin-walled nature of the prestressed aqueduct and the high peak value and frequency of the underwater blast shock wave. Therefore, the failure mechanism of the prestressed aqueduct to underwater explosion is examined. Subsequently, a fragility analysis of a large-span prestressed aqueduct subjected to underwater explosions is performed using a probabilistic method for safety assessment with the index of through-crack length ratio and damage area ratio. The fragility analysis procedure of the large-span prestressed aqueduct to the underwater explosion is introduced herein for the first time in literature. The damage limit states are proposed based on various damage patterns and index values derived from extensive computational conditions. The fragility curves with different indices of through-crack length ratio and damage area ratio under 2 m of explosive depth are also compared. The fragility curves of the prestressed aqueduct to the underwater explosion with different explosive distances of 0–2 m are developed utilizing the Artificial Neural Network algorithm. The findings indicate that the explosive scenarios involving an explosive weight of over 5.6 kg cause a significant threat to the integrity of the prestressed aqueduct with the probability of severe damage reaching 100 %. The explosive situations with explosive weight of less than 1.6 kg have a minimal effect. The research findings can serve as a reference for the safety assessment of prestressed aqueducts subjected to underwater explosions.